1988
DOI: 10.1159/000138484
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Nicotine from a Cigarette That Does Not Burn Tobacco

Abstract: Ten smokers participated in a study to compare the absorption of nicotine from the smoke aerosol of a new cigarette that heats, but does not burn tobacco (test) with a cigarette that burns tobacco (reference). The average plasma nicotine concentrations obtained by the 7th test cigarette (13 ng/ml) and 7th reference cigarette (24 ng/ml) were proportional to the nicotine yielded by the two cigarettes as determined under Federal Trade Commission machine-smoking conditions. These data demonstrate that the smoke ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The different responses noted in the earlier study appear to be due to the low availability of nicotine from the specially designed reference cigarette used in that study. The similarity noted here between test and reference has been confirmed in additional animal inhalation studies , and in a clinical trial (deBethizy et al, 1988). Cigarettes that only heat tobacco thus do not differ from cigarettes that burn tobacco, in terms of the bioavailability of nicotine.…”
Section: Discussionsupporting
confidence: 67%
“…The different responses noted in the earlier study appear to be due to the low availability of nicotine from the specially designed reference cigarette used in that study. The similarity noted here between test and reference has been confirmed in additional animal inhalation studies , and in a clinical trial (deBethizy et al, 1988). Cigarettes that only heat tobacco thus do not differ from cigarettes that burn tobacco, in terms of the bioavailability of nicotine.…”
Section: Discussionsupporting
confidence: 67%
“…Strong species differences or other physical and chemical mechanisms may provide the explanation for the differences in the studies. Recent work with human subjects (deBethizy et al, 1988) has shown no differences between test and reference cigarettes in terms of resultant plasma nicotine concentrations, plasma cotinine, and the plasma cotinine-tonicotine ratio. Plasma nicotine was shown to be directly proportional to the nicotine yield of the cigarette.…”
Section: Discussionmentioning
confidence: 98%
“…The ratio of cotinine to nicotine indicates that the nicotine metabolism was approximately similar in the test and reference groups, with large variability in the data. Recent work in human subjects (deBethizy et al, 1988) has shown no differences between test and reference cigarettes in terms of resultant plasma nicotine concentrations, plasma cotinine, and the plasma cotinine to nicotine ratio. Plasma nicotine was shown to be directly proportional to the nicotine yield of the cigarette.…”
Section: Fig 1 I-continuedmentioning
confidence: 97%